The diet of black-backed jackal (Canis Mesomelas) on two contrasting land-use types in the Eastern Cape Province, South Africa and the validation of a new analytical method of mammalian hair identification - Forbes, Ross William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
Diet assessments are critical for understanding the foraging behaviour, habitat use and trophic separation of mammalian predators and are vital for gaining insight into how predators influence prey populations. The aim of this research was to qualitatively describe the diet of black-backed jackals (Canis mesomelas, Schreber 1775) using scat analysis on two contrasting land-use types in the Eastern Cape Province, South Africa. Scats were collected on a monthly basis from November 2009 to October 2010 from two game reserves (Great Fish River Reserve and Shamwari Private Game Reserve) and two neighbouring livestock farms. The relative frequency of occurrence of mammal hair (33 "“ 47 %) and vegetation (32 "“ 45%)dominated jackal diet throughout the year across the four study sites. Other important prey items included invertebrates (8 "“ 21 %) and fruit and seeds (3 "“ 11 %). Birds and reptiles constituted â‰¤ 2 % of the diet and were only recorded on the game reserves. Significant seasonal dietary shifts were observed on the game reserves but not on the farms. Fruit and seeds were significantly more frequent in the diet during autumn at Great Fish River Reserve and invertebrates were significantly less common in the diet during winter on both reserves. In addition, vegetation was significantly more common in the diet during winter at Shamwari Private Game Reserve. The significant temporal variation of certain prey items is testament to black-backed jackals being opportunistic generalists, foraging on those food items which are most abundant, accessible and energetically beneficial. Land-use type also influenced the diet of black-backed jackals with significantly more invertebrates and, fruit and seeds being recorded on the game reserves than on the farms. By contrast, significantly more mammal hair and vegetation were present in the diet on the farms compared with the game reserves. The mammalian component of the diet was dominated by ruminants and rodents on the game reserves and by ruminants and livestock on the farms. The presence of livestock in the diet of black-backed jackals on the farms highlights their potential impact on the livestock industry in the region and may assist farmers in determining which predators are responsible for stock loss. Previous approaches for identifying mammalian hairs from predator scats have utilised dichotomous keys and reference collections but these are often time-consuming and require a trained individual to carry out the identification. Thus, I also tested the efficacy of an automated pattern recognition programme (HairSnap) for identifying mammalian hairs from black-backed jackal scats. The overall accuracy of the programme was 38 % with black-backed jackal, Greater kudu (Tragelaphus strepsiceros) and striped polecat (Ictonyx striatus) hairs being accurately identified more often (70 "“ 80 %) than any other species tested. It is likely that both the size and species composition of the sample resulted in the poor accuracy of the programme. However, with the implementation of several improvement measures (e.g. adjustment of the algorithm) the programme may offer a superior, bias-free method of mammalian hair identification. The dietary information gathered here furthers our knowledge of the biology of the blackbacked jackals, especially in the locally important thicket biome. Moreover, understanding their foraging habits allows for more effective management of the species on both game reserves and farmlands. I recommend that future research should focus on quantitatively assessing the diet of black-backed jackals in the Eastern Cape Province and elsewhere. This will compliment the dietary description provided in this study and may offer a biologically more meaningful indication of the relative importance of the prey items.
Keywords: Black-backed jackal -- South Africa -- Eastern Cape; Jackals -- South Africa -- Eastern Cape; Jackals -- Food; Mammals -- Identification